2013
DOI: 10.1021/ja4085385
|View full text |Cite
|
Sign up to set email alerts
|

1,6-Carbene Transfer: Gold-Catalyzed Oxidative Diyne Cyclizations

Abstract: In the presence of a gold catalyst an unprecedented oxidative cyclization of diynes takes place. The reaction cascade is initiated by an oxygen transfer from a N-oxide onto a gold-activated alkyne. The formed α-oxo carbene is transferred across the second alkyne yielding a stabilized vinyl carbene/cation. Alkyl migration or sp(3)-CH insertion then terminates the catalytic cycle by formation of highly substituted functionalized indenones. A 1,6-carbene shift could be supported by the oxidation of the vinyl carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(68 citation statements)
references
References 39 publications
3
63
0
2
Order By: Relevance
“…Hashmi reported that α‐oxo gold carbenes could react with tethered alkynes to yield alkenyl metal carbenes through a 1,6‐carbene transfer [Scheme , Eq. (1)] . Such a 1,6‐carbene transfer was noted also for rhodium catalysts and for the generation of several gold carbenes that were generated from 1,3‐acyloxy shifts of propargyl acetates .…”
Section: Introductionmentioning
confidence: 78%
“…Hashmi reported that α‐oxo gold carbenes could react with tethered alkynes to yield alkenyl metal carbenes through a 1,6‐carbene transfer [Scheme , Eq. (1)] . Such a 1,6‐carbene transfer was noted also for rhodium catalysts and for the generation of several gold carbenes that were generated from 1,3‐acyloxy shifts of propargyl acetates .…”
Section: Introductionmentioning
confidence: 78%
“…For the mechanism we suggest the following pathway: oxidation of 1 with the N ‐oxide in the presence of the gold catalyst generates the α,α‐diketo gold carbene II . Then, a cation/carbene intermediate III might be formed through 1,6 carbene transfer …”
Section: Resultsmentioning
confidence: 99%
“…Recently, a gold‐catalyzed oxidative cyclization of aryl ortho ‐diynes 1 was reported. In the presence of N ‐oxides, a 1,6‐carbene transfer initiated a reaction cascade that delivered functionalized indenones (Scheme a) after the trapping of the final carbene/cation intermediate through a 1,2‐alkyl shift . A related reactivity pattern was observed with aromatic diynes bearing one terminal propargylic acetate as carbene precursor .…”
Section: Introductionmentioning
confidence: 91%
“…In 2013, we found an unexpected reaction pathway to obtain gold carbene by using N-oxides in diyne systems. [9] N-oxides can be used instead of diazo compounds to access α-oxo gold carbene, too. [3a,d,10] Our group reported on a 1,6-carbene shift of a initially formed α-oxo gold carbene generated by oxygen transfer from N-oxides which was transferred over a tethered alkyne.…”
mentioning
confidence: 86%
“…According to our previous work and the work of Zhang, [14,9] a proposed reaction mechanism [15] is shown in Scheme 3. The first step starts with π-activation of COMMUNICATIONS asc.wiley-vch.de the terminal alkyne in the presence of the gold catalysts.…”
mentioning
confidence: 99%